1987
DOI: 10.1093/ageing/16.5.285
|View full text |Cite
|
Sign up to set email alerts
|

Altered Water Excretion In

Abstract: The renal and vasopressin (AVP) response to a standard oral water load (20 ml/kg) was examined in a group of water-replete healthy elderly men (n = 6). Two groups, respectively, of water-replete and water-deprived young healthy volunteers acted as controls. After 2 h, the old group had excreted 41 +/- 2.4% (mean +/- SEM) of the water load compared to 100.7 +/- 8.8% in the water-replete young group and 70 +/- 3.8% in the water-deprived young group (P less than 0.01). Similarly, peak diuresis (7.01 +/- 0.48 ml/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 0 publications
0
46
0
1
Order By: Relevance
“…Basal vasopressin secretion is probably normal in elderly subjects. However, both normal and reduced responses to water deprivation have been described [18,19]. Although the ability to conserve salt is maintained, there is a delay in balancing losses [20].…”
Section: Renal Systemmentioning
confidence: 99%
“…Basal vasopressin secretion is probably normal in elderly subjects. However, both normal and reduced responses to water deprivation have been described [18,19]. Although the ability to conserve salt is maintained, there is a delay in balancing losses [20].…”
Section: Renal Systemmentioning
confidence: 99%
“…This population is at risk for dehydration because the elderly have a diminished sensation of thirst and are less able to regulate their¯uid balance (Crowe et al, 1987;Phillips et al, 1991). If left untreated, dehydration can result in death in many cases (Mahowald & Himmelstein, 1981;Warren et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that hypodipsia and consequent dehydration may be a major problem for elderly people in long-term care [1], In the fit elderly Philips et al [2] re ported that thirst was reduced and it is known that water conservation is impaired in ageing [2][3][4], We have previously pre sented a preliminary survey which showed that only 7 out of 58 long-stay residents had an osmolality of less than 296 mosm/kg [5], The reasons for the hyperosmolar state were not clear but it was possibly linked to chronic confusion. No attempt was made to measure the fluid input.…”
mentioning
confidence: 99%